Personhood Beyond Humanism Animals, Chimeras, Autonomous Agents and the Law - Pietrzykowski, Tomasz (SpringerBriefs in Law, 2018)
This book explores the legal conception of personhood in the context of contemporary challenges, such as the status of non-human animals, human-animal biological mixtures, cyborgisation of the human body, or developing technologies based on artificial autonomic agents. It reveals the humanistic assumptions underlying the legal approach to personhood and examines the extent to which they are undermined by current and imminent scientific and technological advances. Further, the book outlines an original conception of non-personal subjecthood so as to provide adequate normative solutions for the problematic status of sentient animals and other kinds of entities. Arguably, non-personal subjects of law should be regarded as holding one right, and only one right - the right to be taken into account.